Pard3 suppresses glioma invasion by regulating RhoA through atypical protein kinase C/NF‐κB signaling. (7th March 2019) - Li, Junjun; Xu, Hao; Wang, Qiangping; Fu, Peng; Huang, Tao; Anas, Omarkhalil; Zhao, Hongyang; Xiong, Nanxiang
Abstract: Partitioning defective protein 3 (Pard3) has been reported to inhibit the progression of numerous human cancer cell types. However, the role of Pard3 in glioma progression remains unclear. In this study, the expression of Pard3 was measured in human gliomas of different grades by both quantitative polymerase chain reaction and Western blotting. The effect of Pard3 on glioma progression was tested using cell counting kit‐8 assays, EdU assays, colony formation assays, cell migration, and invasion assays and tumor xenografts. The effect of Pard3 on Ras homolog family member A (RhoA) protein levels, subcellular localization, and transcriptional activity was measured by immunoblotting and immunofluorescence. Our results indicate that Pard3 functions as a tumor suppressor in gliomas and that the loss of Pard3 protein is strongly associated with a higher grade and poorer outcome. Pard3 overexpression inhibits glioma progression by upregulating RhoA protein levels. However, the level of GTP‐RhoA protein remained unchanged. Further evidence demonstrates that Pard3 regulates RhoA protein levels, subcellular localization and transcriptional activity by activating atypical protein kinase C/NF‐κB signaling. Mouse modeling experiments show that Pard3 overexpression inhibits glioma cell growth in vivo. Taken together, these findings identify RhoA as a novel target of Pard3 in gliomas and substantiate a novel regulatory role for Pard3 in glioma progression. This study reveals that Pard3 plays an inhibitory role in gliomas by regulating RhoA, which reveals a potential benefit for Pard3 activators in the prevention and therapy of gliomas. Abstract : Overexpression of partitioning defective protein 3 inhibits glioma cell proliferation, migration, and invasion.